1986
DOI: 10.1111/j.1432-1033.1986.tb09392.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on ribosomal peptidyltransferase. The behaviour of the inhibitor blasticidin S

Abstract: In a cell-free system derived from Escherichiu coli, the reaction between A c [~H ] P~~-~R N A and puromycin (S) is inhibited by blasticidin S (I). In this reaction A c [~H ] P~~-~R N Ais part of the A~[~HlPhe-tRNA-poly(U)-ribosome complex (C). After preincubating the complex C with I and then adding S, the degree of inhibition is greater than that observed when C reacts with a mixture of S and I. Without preincubation, the inhibition is competitive giving a Ki of 2 x M. After preincubation the inhibition beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
13

Year Published

1989
1989
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 19 publications
(7 reference statements)
1
36
1
13
Order By: Relevance
“…In agreement with a previous study performed at 10 mM Mg 2ϩ and 100 mM NH 4 ϩ (6), analysis of the initial slopes by DR plotting (1/(k obs ) o versus 1/[S]) and slope-replotting (slope of DR plots versus [I]), not shown, confirms that blasticidin S behaves as a competitive inhibitor over a narrow range of inhibitor concentrations ([I] Ͻ 3 ϫ K i ). The K i value found in the present study is approximately two-times higher than that reported in this earlier report (6). In contrast, our analysis of the late slopes revealed a partial-noncompetitive inhibition.…”
Section: Inhibition Of Peptide Bond Formation At Low Concentrations Ocontrasting
confidence: 57%
See 4 more Smart Citations
“…In agreement with a previous study performed at 10 mM Mg 2ϩ and 100 mM NH 4 ϩ (6), analysis of the initial slopes by DR plotting (1/(k obs ) o versus 1/[S]) and slope-replotting (slope of DR plots versus [I]), not shown, confirms that blasticidin S behaves as a competitive inhibitor over a narrow range of inhibitor concentrations ([I] Ͻ 3 ϫ K i ). The K i value found in the present study is approximately two-times higher than that reported in this earlier report (6). In contrast, our analysis of the late slopes revealed a partial-noncompetitive inhibition.…”
Section: Inhibition Of Peptide Bond Formation At Low Concentrations Ocontrasting
confidence: 57%
“…Consistently, blasticidin S has been found to inhibit the binding of CACCA (Phe) to the A-site of ribosomes (3) and to compete with designated A-site inhibitors (4). In addition, the inhibition of peptidyl-or AcPhe 1 -puromycin synthesis by this antibiotic shows a competitive phase in concert with noncompetitive or mixed-noncompetitive phases (5,6), a fact supporting the notion that blasticidin S influences, at least transiently, the affinity of the A-site. Further support derives from chemical probing studies in Escherichia coli ribosomes (7), suggesting that blasticidin S protects A2439, one of the three nucleosides in domain V of 23 S rRNA, which show altered chemical reactivity on removal of the aminoacyl group from A-site-bound tRNAs (8).…”
supporting
confidence: 52%
See 3 more Smart Citations